2006
DOI: 10.1088/0031-9155/51/23/009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of a MOSFET dosimeter for proton dose measurements

Abstract: The metal oxide semiconductor field-effect transistor (MOSFET) dosimeter has been widely studied for use as a dosimeter for patient dose verification. The major advantage of this detector is its size, which acts as a point dosimeter, and also its ease of use. The commercially available TN502RD MOSFET dosimeter manufactured by Thomson and Nielsen has never been used for proton dosimetry. Therefore we used the MOSFET dosimeter for the first time in proton dose measurements. In this study, the MOSFET dosimeter wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…Equation ͑3͒ can provide a qualitative explanation to the observed LET dependence in MOSFET detectors in measuring the dose of a Bragg peak. 13 It shows that for a given electric field with a fixed magnitude and orientation, i.e., a fixed value for the parameters , the fraction of charge pairs escaping recombination would decrease as the number of charge pairs created by the particle N 0 increases. At any point along the particle track, N 0 should be proportional to the LET at the point.…”
Section: Iic Let Dependencementioning
confidence: 96%
See 4 more Smart Citations
“…Equation ͑3͒ can provide a qualitative explanation to the observed LET dependence in MOSFET detectors in measuring the dose of a Bragg peak. 13 It shows that for a given electric field with a fixed magnitude and orientation, i.e., a fixed value for the parameters , the fraction of charge pairs escaping recombination would decrease as the number of charge pairs created by the particle N 0 increases. At any point along the particle track, N 0 should be proportional to the LET at the point.…”
Section: Iic Let Dependencementioning
confidence: 96%
“…12 In a recent study of a MOSFET dosimeter for proton therapy, the dosimeter was found to undervalue the dose substantially around the Bragg peak where LET increases dramatically. 13 As will be shown, although the method for range verification under study here uses only the dose ratio rather than the dose itself, the LET effect will not cancel out. A correction method had to be developed for accurately calculating the response of MOS-FET detectors to proton beams.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations